Praktyka pedagogiczna kontekstem reorganizacji personalnej wiedzy o nauczaniu przyszłych nauczycieli. Propozycja zmiany modelu kształcenia nauczycieli - Michalak, Renata (Instytut Pedagogiki Uniwersytetu Wrocławskiego, 2018)
The article presents reflections on the importance of teaching practice in constructing the professional role of candidates for teachers. Besides, it has stressed the value of the high-quality educational practice in learning and enrichment of the relevant experiences in the process of crystallizing the professional identity of adepts of the art of teaching. The article drew attention to the need of developing their key competences in the course of the academic training that led to achieving self-awareness of being a professional. In addition, the article presents an innovative model of candidates for teachers education based on the implementation of changes in the educational environment.
Keywords: competences; model of teacher training; pedagogical practice; professional identity of teachers; university education